2015
DOI: 10.1039/c4ta04953e
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in organic–inorganic halide perovskite solar cells: mechanisms and material design

Abstract: While energy shortage is always an issue, the impending exhaustion of fossil fuel sources makes it an ever increasingly pressing one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 275 publications
(347 reference statements)
4
120
0
Order By: Relevance
“…[ 1 ] The performance of cells using the perovskite materials [2][3][4][5][6][7][8] has already surpassed that of both conventional dye-sensitized and organic photovoltaics as well as inorganic nanoparticle (including quantum dots)-based solar cells. [9][10][11][12][13][14] This mainly stems from the easy band gap tuning by managing the chemical composition, [ 5,7 ] large optical absorption, high carrier mobility, and very long electron-hole diffusion lengths.…”
Section: Doi: 101002/aenm201502104mentioning
confidence: 99%
“…[ 1 ] The performance of cells using the perovskite materials [2][3][4][5][6][7][8] has already surpassed that of both conventional dye-sensitized and organic photovoltaics as well as inorganic nanoparticle (including quantum dots)-based solar cells. [9][10][11][12][13][14] This mainly stems from the easy band gap tuning by managing the chemical composition, [ 5,7 ] large optical absorption, high carrier mobility, and very long electron-hole diffusion lengths.…”
Section: Doi: 101002/aenm201502104mentioning
confidence: 99%
“…However, exploration of device stability and degradation of the materials has been less studied 12 compared to research on device engineering [13][14] and device physics. [15][16][17][18][19] Nevertheless, the importance of stability is widely recognized, 12 and several studies have examined the stability of perovskite solar cells in humid air using a variety of conditions and device structures. [20][21][22][23][24] For instance, Yang et al found that the identity of the hole transport layer has a dramatic effect on the degradation of triiodide perovskite films using in situ UV-vis measurements, with 2,2',7,7'-tetrakis-(N,N-di-4-methoxyphenylamino)-9,9'-spirobifluorene (Spiro-OMeTAD) and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA) causing more rapid degradation than poly(3-hexylthiophene-2,5-diyl) (P3HT).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] In the case of MAPbI3. and MAPbI3-xClx halide perovskites, the possible relations existing between perovskite properties and processes followed to prepare the material were mainly devoted to features such as morphology and light absorption efficiency, 13,14 since bandgap energy and crystal structure are nearly independent of the preparation procedures (e.g.…”
Section: Introductionmentioning
confidence: 99%